The role of non-aromatizable testosterone metabolite in metabolic pathways - Dušková, M; Pospíšilová, H (Physiological research, 2011)
Dihydrotestosterone (DHT) originates via irreversible reduction of testosterone by catalytic activity of 5alpha-reductase enzyme and it is demonstratively the most effective androgen. Androgens influence adipose tissue in men either directly by stimulation of the androgen receptor or indirectly, after aromatization, by acting at the estrogen receptor. DHT as a non-aromatizable androgen could be responsible for a male type fat distribution. The theory of non-aromatizable androgens as a potential cause of a male type obesity development has been studied intensively. However, physiological levels of DHT inhibit growth of mature adipocytes. In animal models, substitution of DHT in males after gonadectomy has a positive effect on body composition as a testosterone therapy. Thus, DHT within physiological range positively influences body composition. However, there are pathological conditions with an abundance of DHT, e.g. androgenic alopecia and benign prostatic hyperplasia. These diseases are considered as risk factors for development of metabolic syndrome or atherosclerosis. In obese people, DHT metabolism in adipose tissue is altered. Local abundance of non-aromatizable androgen has a negative effect on adipose tissue and it could be involved in pathogenesis of metabolic and cardiovascular diseases. Increased DHT levels, compared to physiological levels, have negative effect on development of cardiovascular diseases. Difference between the effect of physiological and increased level brings about certain paradox.
Keywords: obezita; tuková tkáň; kardiovaskulární nemoci; Humans; androgeny; hyperplazie prostaty; složení těla; Androgens; dihydrotestosteron; krysa rodu Rattus; Dihydrotestosterone; Alopecia; lidé; zvířata; myši; androgenní receptory; Prostatic Hyperplasia; Mice; Cholestenone 5 alpha-Reductase; Cardiovascular Diseases; Male; Testosterone; Receptors, Androgen; Body Composition; Rats; Obesity; Animals; alopecie; cholestenon-5-alfa-reduktasa; mužské pohlaví; testosteron; Adipose Tissue